A New Robust Application for Singularly Perturbed Volterra-Integro Differential Equations - Arslan, Derya (Communications in Mathematics and Applications, 2025)
In this study, we aimed to approximately solve singularly perturbed Volterra-integro differential equation with the Adomian decomposition method. The solution procedure is easy and fast. Firstly, the equation is written in operator form. Then the integral operator is applied to all sides of the equation. The series solution is obtained by applying some operations to the given equation and then converting it into a recurrence relation. Error values show that the solution results obtained for the two applied examples are very close to each other. The proposed method gives successful results with 21 and 23 iterations.